Long-term Cardiac Maintenance Programming: A SINGLE-SITE ANALYSIS of MORE THAN 200 PARTICIPANTS - Christle, Jeffrey W.; Baumgartner, Michaela; Zelger, Otto; Lammel, Christoph; Haller, Bernhard; Bjarnason-Wehrens, Birna; Myers, Jon; Hamm, Larry F.; Froelicher, Victor; Halle, Martin; Pressler, Axel (Journal of Cardiopulmonary Rehabilitation and Prevention, 2021)
Purpose: Greater than 65% of all cardiac mortality is related to coronary artery disease (CAD). Cardiac rehabilitation (CR) aims to reduce cardiovascular risk and number of hospital readmissions. Cardiac maintenance programs (CMPs) are designed to sustain or improve health after completing early CR. Although CMPs are supported by most national health guidelines, few long-term studies on these diverse programs have been performed. Methods: This was a retrospective repeated-measures analysis with case-controlled subanalysis. Within-subject differences for CMP participants were examined between enrollment and last clinical visit. Assessments included medical history, anthropometry, blood analysis, and cardiopulmonary exercise testing. A subset of 20 CMP participants were compared with 20 patients with CAD who chose not to participate in CMP, matched for age, sex, and follow-up duration. Results: A total of 207 patients (60 ± 9 yr, 16% female) were included for the primary analyses. Average follow-up was 6.3 ± 4.8 yr (range 4-20 yr). CMP participants reduced peak workload (1.76 ± 0.56 to 1.60 ± 0.58 W/kg; P <.001) and aerobic capacity (26.1 ± 6.2 to 24.6 ± 7.1 mL/kg/min; P =.003). High-density lipoprotein-cholesterol increased significantly (48 ± 12 to 51 ± 14 mg/dL; P <.001), whereas all other metabolic risk factors remained unaffected. Matched controls had higher functional capacity (2.35 ± 0.81 vs 1.56 ± 0.52 W/kg; P <.001) and lower body mass index (25.3 ± 3.6 vs 28.6 ± 3.9 kg/m2) at baseline, but no significant differences with respect to long-term efficacy were observed. Conclusions: Long-term participation in CMP did not result in maintaining functional capacity or cardiovascular risk profile in patients with CAD. However, compared with matched nonparticipants, CMP participants (are more deconditioned at baseline) but do not seem to deteriorate as quickly.
CRIS-Team Scopus Importer:2023-03-08
Keywords: cardiac rehabilitation; coronary artery disease; exercise; heart failure; physical activity